Bih guzīn-i ʿAlī-nāma : Kuhantarīn manẓūma-yi Shīʿi-yi Fārsī - Rabīʿ (Miras Maktoob, ISBN: 9789004365452., 2019)
Until the discovery of the Persian ʿAlī-nāma , Ibn Ḥusām's Khawarān-nāma (830/1427) was believed to be the oldest Persian epic poem involving the often wondrous exploits of ʿAlī b. Abī Ṭālib and the beginnings of Shīʿism. The Khawarān-nāma takes its inspiration from Firdawsī's Shāh-nāma , but then adapted to fit the Shīʿī theme, with ʿAlī and his companions often taking the place of Rustam and other heroes. The ʿAlī-nāma , extant in one manuscript in Konya, is a much older poem on the same subject. Composed by someone using the alias of Rabīʿ, it was completed in 482/1089 in Khurāsān, just seventy years after the completion of Firdawsī's Shāh-nāma . The text is important because long before others, it acknowledges the heroes of the Shāh-nāma , some of whom were actually written into the script. Different from the edition by Omidsalar (2010), this edition only reproduces verses deemed worthy of Rabīʿ, rejecting two-thirds as the work of some unknown 'poetaster'.